Structural basis for Glycan-receptor binding by mumps virus hemagglutinin-neuraminidase - Forgione, Rosa Ester (Sci Rep, 2020)
Mumps virus is one of the main cause of respiratory illnesses in humans, especially children. Among the viral surface glycoproteins, the hemagglutinin – neuraminidase, MuV-HN, plays key roles in virus entry into host cells and infectivity, thus representing an ideal target for the design of novel inhibitors. Here we report the detailed analysis of the molecular recognition of host cell surface sialylated glycans by the viral glycoprotein MuV-HN. By a combined use of NMR, docking, molecular modelling and CORCEMA-ST, the structural features of sialoglycans/MuV-HN complexes were revealed. Evidence for a different enzyme activity toward longer and complex substrates compared to unbranched ligands was also examined by an accurate NMR kinetic analysis. Our results provide the basis for the structure-based design of effective drugs against mumps-induced diseases.